AN ASSESSMENT OF NURSES’ PARTICIPATION IN HEALTH PROMOTION: A KNOWLEDGE, PERCEPTION, AND PRACTICE PERSPECTIVE - Thuraya Taleb Albiji, Dalal Abdullah Alshammari, Mona Mohammed Alshammari, Tiflah Mohammed Alshammari, Munira Dughayyim Alshammari, Mashael Suliman Aljameeli, Mohammed Furaih Alanazi (Chelonian Research Foundation, 2023)
Background: Health promotion (HP) is crucial for addressing health inequalities and enhancing healthcare quality. Nurses play a vital role in delivering HP services, yet their competence in this area needs further investigation. This study aims to explore the impact of HP knowledge and perceptions on nurses' HP practices. Methods: A self-administered questionnaire was used to survey 184 nurses randomly selected from a tertiary hospital. The questionnaire covered demographics, HP knowledge, perceptions, and practices. Data were analyzed using IBM SPSS Statistics, Version 26.0. Results: The analysis revealed significant relationships between participants' demographics and their level of HP knowledge. Furthermore, significant associations were found between holistic disease knowledge and effective patient care (p = 0.001) and between awareness of patient education importance and encouraging healthy lifestyles (p < 0.001). Conclusion: Nurses' HP knowledge strongly influenced their perceptions and practices in HP. It is essential for healthcare organizations and educational institutions to integrate robust HP training into nursing education and ongoing professional development. Keywords: Nurses, Health promotion, Practice